2020
DOI: 10.5194/egusphere-egu2020-698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid assessment of floating macroplastic transport in the Rhine

Abstract: <p>Most marine litter pollution is assumed to originate from land-based sources, entering the marine environment through rivers. To better understand and quantify the risk that plastic pollution poses on aquatic ecosystems, and to develop effective prevention and mitigation methods, a better understanding of riverine plastic transport is needed. To achieve this, quantification of riverine plastic transport is crucial. Here, we demonstrate how established methods can be combined to provide a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…van Emmerik, Strady, et al (2019) sampled macroplastics (>5 cm) from the surface to 1–1.3 m depth in the Saigon River of Vietnam and found 88%–90% of plastics in the upper 0.5 m. In Jakarta (Indonesia), van Emmerik, Loozen, van Oeveren, Buschman, and Prinsen (2019) reported macroplastic (>1.5 cm) concentrations that were on average five times higher in the uppermost 0.425 m of the river than between 0.425 and 1 m deep. For the lateral distribution of floating macroplastics across river widths, van Emmerik, Loozen, et al (2019) observed plastics concentrated in the center in mostly channelized and straight rivers of Jakarta, but other studies showed more horizontal variability (van Emmerik, Loozen, et al, 2019; van Emmerik, Tramoy, et al, 2019; Vriend et al., 2020); they suggest that in addition to flow velocities, distributions may be affected by flow and tidal dynamics, wind directions and speed, river geometries, and navigation activities. van Calcar and van Emmerik (2019) synthesized the literature on surface macroplastic transport for over 20 rivers, showing different spatial variability patterns of plastic across river widths, ranging from the majority of plastic concentrated in the center or at side sections to cases with almost equal cross‐sectional distributions.…”
Section: Introductionmentioning
confidence: 97%
“…van Emmerik, Strady, et al (2019) sampled macroplastics (>5 cm) from the surface to 1–1.3 m depth in the Saigon River of Vietnam and found 88%–90% of plastics in the upper 0.5 m. In Jakarta (Indonesia), van Emmerik, Loozen, van Oeveren, Buschman, and Prinsen (2019) reported macroplastic (>1.5 cm) concentrations that were on average five times higher in the uppermost 0.425 m of the river than between 0.425 and 1 m deep. For the lateral distribution of floating macroplastics across river widths, van Emmerik, Loozen, et al (2019) observed plastics concentrated in the center in mostly channelized and straight rivers of Jakarta, but other studies showed more horizontal variability (van Emmerik, Loozen, et al, 2019; van Emmerik, Tramoy, et al, 2019; Vriend et al., 2020); they suggest that in addition to flow velocities, distributions may be affected by flow and tidal dynamics, wind directions and speed, river geometries, and navigation activities. van Calcar and van Emmerik (2019) synthesized the literature on surface macroplastic transport for over 20 rivers, showing different spatial variability patterns of plastic across river widths, ranging from the majority of plastic concentrated in the center or at side sections to cases with almost equal cross‐sectional distributions.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have been published on floating riverine litter transport in the Dutch Rhine delta. Estimates of plastic exports by Dutch rivers range between 1.3 -6300 kg per day (Vriend et al, 2020b, van der Wal et al, 2015Lebreton et al, 2017). Tauw) to determine plastic transport.…”
Section: Floating Littermentioning
confidence: 99%
“…Floating litter concentrations in these cities were found to be 111-133 items per kilometre of canal, with pollution hotspots around more populous areas within the cities. (Vriend et al, 2020b).…”
Section: Floating Littermentioning
confidence: 99%
“…In future works, more details may be determined using a combination of a visual counting method with hydrodynamic modelling [57]. Insight into macroplastic transport distance may be also gained by modifications of the existing hydrodynamic models used for simulations of the transport of large woody debris [e.g., 44,58] as well as by long-term observations of plastic accumulation on riverbanks [59].…”
Section: Macroplastic Transportmentioning
confidence: 99%
“…Previous works on surface and subsurface storage of macroplastic debris used hand collection and sieve analysis for estimation of plastic abundance (Table 1). Analysed samples were collected from quadrats [30,34,62,63], circles [64] or transects [65] delimited parallel or perpendicular to the shoreline of river channel or reservoir [59]. Obtained results were usually described as number of plastic debris items or their mass per surface area (m 2 ) of sampled plot (Table 1), which is useful for estimation of plastic abundance in contemporary surface sediments, but does not allow for reliable comparison with volumetric samples of sediments taken from cores or river banks.…”
Section: Macroplastic Storagementioning
confidence: 99%